2023
DOI: 10.30935/ojcmt/13355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pre-service teachers’ digital skills and ICT competencies in context of the demands of the 21st century

Abstract: 21st century has seen the emergence of digital skills as a crucial ability with profound effects on employment, education, and social relationships, among other facets of life. The best talents to teach are the subject of study by those who establish educational policies. The goal of this study is to examine the relationship between information and communication technology competency (ICTC) and digital abilities. It focuses on which of the digital skills sub-dimensions has a greater impact on ICTC and how this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Numerous studies have investigated ICTCs of pre-service teachers, their perceptions of these competencies, and the factors that influence their incorporation of ICT into their instructional methodologies. The evaluation of pre-service teachers' competencies and digital skills has been conducted within the framework of the challenges presented by the 21 st century (Niyazova et al, 2023). The research revealed a significant correlation between ICT proficiency and digital skills, indicating a strong interdependence between these domains and their essentiality in facilitating effective pedagogy in the era of digital technology.…”
Section: Information and Communication Technology Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated ICTCs of pre-service teachers, their perceptions of these competencies, and the factors that influence their incorporation of ICT into their instructional methodologies. The evaluation of pre-service teachers' competencies and digital skills has been conducted within the framework of the challenges presented by the 21 st century (Niyazova et al, 2023). The research revealed a significant correlation between ICT proficiency and digital skills, indicating a strong interdependence between these domains and their essentiality in facilitating effective pedagogy in the era of digital technology.…”
Section: Information and Communication Technology Competenciesmentioning
confidence: 99%
“…SCC is only It is plausible that the level of communication competence directly impacts the confidence of pre-service teachers in navigating and implementing ICT tools. When pre-service teachers can effectively communicate, they can more easily understand and apply the information and training they receive in ICT, leading to higher ICTC (Haslaman et al, 2023;Niyazova et al, 2023). Moreover, competence in communication may also assist in peer-to-peer learning, where teachers can share experiences, challenges, and solutions in ICT utilization, creating an atmosphere of collaborative learning that can enhance ICTC (Aslan & Zhu, 2017).…”
Section: Competence For Communication Skills (Comp)mentioning
confidence: 99%
“…The role of science education is integral to developing the scientific literacy and comprehension of individuals (Al Sultan et al, 2021;Niyazova et al, 2023). Nonetheless, conventional pedagogical methodologies may not sufficiently engage students in the contemporary digitally interconnected world.…”
Section: Introductionmentioning
confidence: 99%